A Needs Analysis for Developing a Flipbook-Based E-Module Integrating Palembang Puppet Heritage in Grade 12 Indonesian Language Learning - Agung Prihatmoko Prihatmoko; Nurhayati Nurhayati; Zahra Alwi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Palembang Wayang is a local cultural heritage that is increasingly unfamiliar to younger generations. Integrating this heritage into Indonesian language instruction—especially Grade 12 historical narrative text learning—may strengthen cultural awareness while improving students’ comprehension. This study employed a qualitative descriptive design as the needs-analysis stage of an RD process. Data were collected at SMA Unggul Islam Al-Fahd, South Sumatra, through a semi-structured interview with one Indonesian language teacher and questionnaires (Likert-scale and open-ended items) completed by 57 Grade 12 students. Data were analyzed thematically to identify users’ needs, deficiencies in existing resources, and desired features for digital learning media. Most students reported difficulties in learning historical narrative texts, particularly in identifying key information and interpreting values embedded in the text. Existing learning resources (textbooks and worksheets) were perceived as insufficiently engaging and not fully effective in supporting independent learning. Both students and the teacher strongly supported the development of an innovative, interactive e-module featuring Palembang Wayang historical narratives, enriched with attractive visuals, multimedia elements, clear learning guidance, and structured assessments. The findings indicate an urgent need for culturally contextualized digital teaching materials. A flipbook-based e-module is expected to enhance engagement and comprehension while supporting local cultural preservation, providing a grounded basis for subsequent design, development, and field testing stages.